Analysis of 4Cs-Oriented Learning Development Teacher Elementary School Post-Covid-19 Pandemic - Dwi Yulianti; Pramudiyanti (Journal of Adaptive Education, 2025)
An analysis of the development of 4Cs-oriented learning for elementary school teachers in the post-COVID-19 pandemic needs to be carried out to determine the level of success in implementing learning during the Covid-19 pandemic while maintaining the quality of learning outcomes oriented to 4Cs skills. These four skills form the basis of student readiness in dealing with the rapid development of science and technology that is occurring in the 21st century. The results of a preliminary study by researchers on nine SD Gugus Raden Intan Kec. Candipuro, South Lampung Regency, Indonesia, found three main problems (1) the learning objectives represented in the learning outcomes of students were not 4Cs oriented: (2) teachers in implementing online learning during the pandemic were not oriented towards achieving 4Cs skills. (3) teachers have not made professional development demands to develop interactive media, interesting methods, and several learning systems that accommodate 4Cs skills oriented learning effectiveness during a pandemic. The sample in this study involved 27 lower grade teachers who taught grades 1, 2, and 3 at SD Gugus Raden Intan Kec. Candipuro, South Lampung Regency, Indonesia. The focus of learning development analysis in this study aims to obtain an intervention that can help improve teacher competence in developing learning that is oriented towards the achievement of the 4Cs skills after the Covid-19 Pandemic.